MODERN PARADIGM OF THE PREGNANT-INVOLVING PHARMACOLOGICAL STUDY: RISK ASSESSMENT, ETHICAL PRINCIPLES AND REGULATORY ASPECT - K. A. Lutsevich; O. V. Reshetko; T. S. Lutsevich (Педиатрическая фармакология, 2014)
This article is dedicated to the issue of studying drug efficacy and safety in pregnant women, i.e. to their participation in clinical studies. The authors emphasize that lack of evidence base on drug use makes physicians helpless against diseases and gestational pathological conditions. The authors demonstrate results of the completed clinical studies involving pregnant women. In this article, they analyze possible risks and ethical complications of pregnant women taking part in clinical studies, as well as modern possibilities of medicine and legislative base of a range of countries, which allow minimizing risks of taking part in a study both for mothers and their fetuses. The authors demonstrate that the international experience of resolving ethical and legal issues of clinical studies among children may facilitate settlement of many problems of this issue.